Pain sensitivity mediates the relationship between empathy for pain and psychopathic traits - Dimana V. Atanassova; Inti A. Brazil; Christiaan E. A. Tomassen; Joukje M. Oosterman (Scientific Reports)
Abstract Psychopathic traits and antisocial behavior show a well-documented relationship with decreased empathic processing. It has been proposed that a reduced own experience of pain leads to perceiving others’ pain as less severe, which potentially facilitates exploitative, aggressive behavior towards others. We evaluated the link between psychopathic traits, experimental pain sensitivity and empathy for pain in a community sample (n = 74). Participants rated images depicting painful situations through either a self-centered or other-oriented perspective. Psychopathic traits (Interpersonal, Affective, Lifestyle and Antisocial) were assessed with the Self-Report Psychopathy Scale, and pain threshold (cold, electrical, pressure) and tolerance (cold, electrical) were measured. A Bayesian Structural Equation Modelling approach indicated that self-centered pain estimates and sensitivity to electrical pain predicted judgments of others’ pain (‘pain empathy’). The superordinate psychopathy factor, encompassing the overlap in underlying features of the construct, was shown to indirectly affect pain empathy through the mediating role of electrical pain sensitivity. These results provide support for the notion that a reduced sensitivity to own pain underlies diminished pain empathy, and may hold important implications for understanding the mechanisms of antisocial behavior in psychopathy.